How to Assess the Biomechanical Risk Levels in Beekeeping. Issue 2 (2nd April 2016) - Maina, G.; Rossi, F.; Baracco, A.
ABSTRACT: Beekeepers are at particular risk of developing work-related musculoskeletal disorders, but many of the studies lack detailed exposure assessment. To evaluate the biomechanical overload exposure in a specific farming activity, a multitasking model has been developed through the characterization of 37 basic operational tasks typical of the beekeeping activity. The Occupational Repetitive Actions (OCRA) Checklist and the National Institute for Occupational Safety and Health (NIOSH) Lifting Index methodologies have been applied to these elementary tasks to evaluate the exposure, and the resulting risk indices have been time-weighted averaged. Finally, an easy access, computer-assisted toolkit has been developed to help the beekeepers in the biomechanical risk assessment process. The risk of biomechanical overload for the upper limbs ranges from acceptable (maintenance and recovery of woody material and honey packaging with dosing machine tasks) to high (distribution of the top supers) risk level. The risk for back injury is always borderline in women and increases with exposure time, whereas it ranges from acceptable to borderline in men. The definition of the biomechanical risk levels allows for planning of corrective actions aimed at preventing and reducing the risk of musculoskeletal disorders through engineering, administrative, and behavioral interventions. The methodology can be used for risk assessment in other mainly manual agricultural activities.